EFEKTIFITAS PENDIDIKAN AKHLAK (Pengembangan Akhlakul Karimah di Madrasah Ibtidaiyah Matha’ul Anwar) - Topik Topik (Tarbiya Islamica, 2017)
Education in essence does not only direct students to cognitive aspects, but affective and psychomotor aspects also need to be developed to make students who have good morals. Therefore, Madrasah Ibtidaiyah Matha'ul Anwar Sekura Village is a relevant institution in fostering the morals of students in the educational process in an effort to create national cadres who have high integrity in the field of character and morals. Apart from that, Madrasah Ibtidaiyah Matha'ul Anwar Sekura Village is an Islamic educational institution whose teaching direction is rooted in Islamic values and has an integral concept of religious and general education. Thus, ordinary students get an Islamic environment that is much needed in the development of akhlakul karimah. Madrasah Ibtidaiyah Matha'ul Anwar Sekura Village is very effective in gradually applying akhlakul karimah in daily life. This is reflected in the familiarity of students with students, students with educators, students with their parents, and students with the community environment.